RNA EDITOR-ENHANCED RNA TRANS-SPLICING - GAO, Guangping; WANG, Jiaming; WANG, Dan (2023)
Aspects of the disclosure relate to compositions and methods for exon replacement in a cell or a subject. In some embodiments, the disclosure relates to isolated nucleic acids (and vectors, such as rAAV vectors) encoding one or more guideRNAs (gRNAs) that target an intron-exon boundary; an intronic sequence having a splice signal; and a donor sequence encoding a gene product of a gene of interest, or portion thereof. In some embodiments, compositions described herein are useful for replacing mutant exons associated with certain diseases, for example Duchen's muscular dystrophy (DMD), cystic fibrosis (CF), spinal muscular atrophy (SMA), Rett syndrome, and mucopolysaccharidosis (MPS).